Scalable production and purification of engineered ARRDC1-mediated microvesicles in a HEK293 suspension cell system - Kristin Luther; Ali Navaei; Leah Gens; Carson Semple; Pearl Moharil; Ilaria Passalacqua; Komal Vyas; Qiyu Wang; Shu-Lin Liu; Lucy Sun; Senthil Ramaswamy; Davide Zocco; et al. (Scientific Reports)
Abstract Engineering of human ARRDC1-mediated microvesicles (ARMMs) as non-viral vehicles for delivery of gene therapies bears the potential to enable novel therapeutic paradigms. We evaluated two scalable strategies to generate ARMMs loaded with protein cargo, by transient transfection or stable cell line-based production. The upstream ARMMs production processes utilized a suspension-adapted HEK293-derived line, termed 5B8. 5B8 cells yielded robust production of ARMMs after transient transfection with the ARMMs loading construct or using a stable cell line containing a transgene that encodes the ARMMs loading cassette, in shake flasks or a stirred tank bioreactor, respectively. ARMMs were purified by ultracentrifugation (small scale) or a combination of TFF and AEX (scalable production). Both purification methods produced comparable ARMMs, in terms of size and payload incorporation. Single particle analysis showed approximately 50% were payload-containing ARMMs. Additionally, an in vivo study was conducted in mice to investigate the half-life and biodistribution of ARMMs administered intravenously. ARMMs showed rapid biodistribution predominantly to the spleen and liver and, to a lesser extent, kidneys, and lungs. The half-life of ARMMs in plasma was 6 ± 0.4 min. Altogether, this work advances knowledge on scale-up of engineered cell-derived vesicles for future in vivo delivery of therapeutic molecules.